2013
DOI: 10.1002/mrm.24964
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of semiautomated MR volumetry using gadoxetic acid–enhanced MRI at hepatobiliary phase for living liver donors

Abstract: Semiautomated liver MR volumetry using hepatobiliary phase gadoxetic acid-enhanced MRI with the quadratic MR image division is a reliable, easy, and fast tool to measure liver volume in potential living liver donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…As proved by Lee et al, semiautomated liver MR volumetry using hepatobiliary‐phase gadoxetic acid‐enhanced MRI was a reliable and fast tool to measure liver volume, comparable to computed tomography (CT) volumetry. We used a computer‐aided semiautomatic liver volumetry software IQQA‐liver (v. 2.0; EDDA Technology, Princeton, NJ) running on the 20‐minute hepatobiliary phase T 1 ‐weighted volumetric interpolated breath‐hold examination sequence, with the following parameters: TR/TE = 4.43/1.53 msec, slice thickness = 2.0 mm, no interslice gap, field of view = 100 × 100 mm, following the administration of gadoxetic acid (0.1 ml/kg; Primovist; Bayer Healthcare, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 95%
“…As proved by Lee et al, semiautomated liver MR volumetry using hepatobiliary‐phase gadoxetic acid‐enhanced MRI was a reliable and fast tool to measure liver volume, comparable to computed tomography (CT) volumetry. We used a computer‐aided semiautomatic liver volumetry software IQQA‐liver (v. 2.0; EDDA Technology, Princeton, NJ) running on the 20‐minute hepatobiliary phase T 1 ‐weighted volumetric interpolated breath‐hold examination sequence, with the following parameters: TR/TE = 4.43/1.53 msec, slice thickness = 2.0 mm, no interslice gap, field of view = 100 × 100 mm, following the administration of gadoxetic acid (0.1 ml/kg; Primovist; Bayer Healthcare, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 95%
“…Regarding liver transplantation, Ringe et al [36] emphasized the role of CT, reporting that this method of imaging of the liver, in combination with dedicated software, plays a key role in the evaluation of candidates for liver donor transplantation: based on the results of liver CT volumetry, 31% of the candidates of this series were excluded as donors. Lee et al [37] reported the usefulness of semi automated liver MR volumetry using hepatobiliary phase gadoxetic acid-enhanced images with the quadratic MR image division to measure liver volume in potential living liver donors; the average volume measurement error of the semi automated MR volumetry was 2.35% ± 1.22%. Zappa et al [38] applied CT volumetry to the evaluation of total and segmental liver regeneration after hepatectomy: CT was able to identify even segmental regeneration, reporting a 64% increase in liver volume from the future remnant 7 d after hepatectomy.…”
Section: Imaging: Which Modality Should Be Chosen?mentioning
confidence: 99%
“…4,6 With specialised software, auto-segmentation of organs is possible. [8][9][10][11][12][13][14] However, CT-based automated segmentation of the liver is challenging because organs with comparable density surround the liver. Automated future remnant liver volumetric analysis has not yet been validated by comparing it with manual slice-by-slice drawing of contours.…”
Section: Introductionmentioning
confidence: 99%